2022
DOI: 10.1002/solr.202200493
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Photothermal COx Conversion

Abstract: Recognizing the emergency of the global climate issue, the current fossil fuel‐based economic structure with massive carbon emission is urgent to be transformed. Catalytic conversion of CO x , as an emerging alternative technology to produce advanced chemicals and fuels, has received enormous attention. Particularly, photothermal CO x conversion, combining the advantages of high efficiency and low pollution, has shown the potential for the production of solar fuels and chemicals, and the progress of this fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 136 publications
0
6
0
Order By: Relevance
“…In light-assisted thermocatalytic reactions, where the thermochemical pathway is the main reaction pathway and the photochemical process enhances the catalytic activity, the reaction process follows the thermochemical pathway and reaction mechanism. 14 Relevant experimental and theoretical studies have demonstrated that the reaction pathway for thermocatalytic CO 2 hydrogenation to methanol after the introduction of Ni is the RWGS pathway. 43,51,62 The reaction pathway of photothermal catalytic synthesis of methanol by CO 2 hydrotreating is proposed here (Figure 13), and the interaction between Ni and In 2 O 3 promotes the formation of the action of overflowing H*, CO 2 adsorbed in oxygen vacancies dissociates to generate a COOH*, which then forms CO*.…”
Section: Xrdmentioning
confidence: 99%
See 1 more Smart Citation
“…In light-assisted thermocatalytic reactions, where the thermochemical pathway is the main reaction pathway and the photochemical process enhances the catalytic activity, the reaction process follows the thermochemical pathway and reaction mechanism. 14 Relevant experimental and theoretical studies have demonstrated that the reaction pathway for thermocatalytic CO 2 hydrogenation to methanol after the introduction of Ni is the RWGS pathway. 43,51,62 The reaction pathway of photothermal catalytic synthesis of methanol by CO 2 hydrotreating is proposed here (Figure 13), and the interaction between Ni and In 2 O 3 promotes the formation of the action of overflowing H*, CO 2 adsorbed in oxygen vacancies dissociates to generate a COOH*, which then forms CO*.…”
Section: Xrdmentioning
confidence: 99%
“…Pure thermal catalysis’ excessive energy consumption and catalyst deactivation concerns can be successfully alleviated by photothermal catalysis . Photothermal catalysis is a catalytic reaction that is driven by the photothermal effect (a combination of the photochemistry and thermochemistry of sunlight), which is present in various catalytic materials (semiconductors, plasma metals, composite catalysts). When light strikes a semiconductor, the incident photons excite the semiconductor at an energy equal to or greater than the band gap, producing electrons and holes; some of the electrons and holes subsequently move to the catalyst’s surface to participate in redox processes . In semiconductors, the photothermal effect is based on the photogenerated carriers that are produced, a portion of the electron–hole pairs dissipate the input energy in the form of radiation (emitted photons) or nonradiation (excited phonons), and heat can be generated by lattice vibrations during nonradiation. , The photothermal conversion efficiency of the catalyst is closely related to the band gap width of the semiconductor, and narrow band gap semiconductors are more efficient in converting light energy into heat energy .…”
Section: Introductionmentioning
confidence: 99%
“…It is challenging to clarify the actual catalytic process and identify the catalytic active sites in photoelectrocatalytic reactions due to the complexity of the reaction environment and the dynamic evolution of the catalyst. [97][98][99][100][101] Especially when the material is subjected to plasmonic catalysis, the catalyst will synergistically affect the actual reaction process. Therefore, the synergistic properties induced by the plasmonic must be further discussed, and the specic role should be gradually claried.…”
Section: Synergistic Properties In Plasmonic Catalysismentioning
confidence: 99%
“…1 This is followed by storage in deep wells below the seabed, with the risk of causing unpredictable ecological consequences if the storage site, for whatever reason, should not be long-term indelible. 2 As an alternative, CO 2 capture and utilization have received much attention, as CO 2 can be used to produce high-value chemicals via chemical transformation 3 or electrocatalytic, 2,4 photocatalytic, 5,6 and photothermocatalytic 7 processes. In this regard, CO 2 has been used as a C 1 building block to produce value-added chemicals (carbon monoxide, methanol, formic acid, formaldehyde, acetic acid, and acetaldehyde), high-energy-density fuels (methane, propane, and ethanol), and precursors for polymers such as ethylene 8 and carbonate.…”
Section: Introductionmentioning
confidence: 99%